Long-term survival analysis of masitinib in amyotrophic lateral sclerosis - Mora, Jesus S.; Bradley, Walter G.; Chaverri, Delia; Hernández-Barral, María; Mascias, Javier; Gamez, Josep; Gargiulo-Monachelli, Gisella M.; Moussy, Alain; Mansfield, Colin D.; Hermine, Olivier; Ludolph, Albert C. (Therapeutic advances in neurological disorders, 2021)
Background: A randomized, placebo-controlled phase III study (AB10015) previously demonstrated that orally administered masitinib (4.5 mg/kg/day) slowed rate of functional decline, with acceptable safety, in amyotrophic lateral sclerosis (ALS) patients having an ALS Functional Rating Scale-revised (ALSFRS-R) progression rate from disease onset to baseline of <1.1 points/month. Here we assess long-term overall survival (OS) data of all participants from study AB10015 and test whether a signal in OS is evident in an enriched patient population similar to that prospectively defined for confirmatory study AB19001. Methods: Survival status of all patients originally randomized in AB10015 was collected from participating investigational sites. Survival analysis (using the multivariate log-rank test and Cox proportional hazards model, with stratification factors as covariates) was performed on the intention-to-treat population and enriched subgroups, which were defined according to initial randomization, baseline ALSFRS-R progression rate and baseline disease severity. Results: A significant survival benefit of 25 months (p = 0.037) and 47% reduced risk of death (p = 0.025) was observed for patients receiving 4.5 mg/kg/day masitinib (n = 45) versus placebo (n = 62) in an enriched cohort with ⩾2 on each baseline ALSFRS-R individual component score (i.e. prior to any complete loss or severe impairment of functionality) and post-onset ALSFRS-R progression rate <1.1 (i.e. exclusion of very fast progressors) [median OS of 69 versus 44 months, respectively; hazard ratio, 0.53 [95% CI (0.31–0.92)]]. This corresponds to the population enrolled in confirmatory phase III study, AB19001. Conclusions: Analysis of long-term OS (75 months average follow-up from diagnosis) indicates that oral masitinib (4.5 mg/kg/day) could prolong survival by over 2 years as compared with placebo, provided that treatment starts prior to severe impairment of functionality. This trial was registered at www.ClinicalTrials.gov under identifier NCT02588677 (28 October 2015).